2018
DOI: 10.1039/c8nr06186f
|View full text |Cite
|
Sign up to set email alerts
|

The structural shift of a DNA template between a hairpin and a dimer tunes the emission color of DNA-templated AgNCs

Abstract: The structural shift of a DNA hairpin-dimer is as important as the DNA sequence in determining the fluorescent properties of DNA-stabilized silver nanoclusters (DNA/AgNCs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 34 publications
4
24
0
Order By: Relevance
“…Therefore, depending on the GC content of the sequence, anchor lengths can be modulated which allows this sensor design to be universal for the detection of various miRNA sequences as demonstrated previously [13]. Moreover, we showed that the emission wavelength of the encapsulated AgNCs could be modulated by altering the secondary structure of DNA/AgNCs [24]. Thus, we investigated whether the secondary structure of DNA/AgNCs influences the photo-stability of emissive AgNCs.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Therefore, depending on the GC content of the sequence, anchor lengths can be modulated which allows this sensor design to be universal for the detection of various miRNA sequences as demonstrated previously [13]. Moreover, we showed that the emission wavelength of the encapsulated AgNCs could be modulated by altering the secondary structure of DNA/AgNCs [24]. Thus, we investigated whether the secondary structure of DNA/AgNCs influences the photo-stability of emissive AgNCs.…”
Section: Resultsmentioning
confidence: 89%
“…Based on our previous study [13,24], we further analyzed the secondary structures of DNA/AgNCs templates using in-gel fluorescence assay, to see whether the secondary structures are correlated to the color of fluorescence. Indeed, we found that the secondary structure of DNA 6C-217-11bp is a dimer, while DNA 6C-27a-3bp generated a hairpin structure (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an important factor affecting the emission of DNA-AgNCs, the modulation of secondary DNA structures was used in the ratio detection system (Shah et al, 2018). Xu et al developed a proportional visual analysis sensor platform for miRNA-21 in cells based on the self-assembly of AgNCs triggered by chain displacement.…”
Section: The Fluorescence Signal Based On Dna Strand Hybridizationmentioning
confidence: 99%
“…[26] Fort his class of AgNCbased sensor, it has been reported that they can be emissive both in am onomeric and dimeric state,d epending on the sequence. [27] We here investigate the impact of AgNC formation on oligonucleotide tertiary structure.S pecifically, we hypothesize that dimerization and oligomerization of short monomeric hairpin DNAs occur upon the reduction of coordinated Ag I .W er eport the first small-angle X-ray scattering (SAXS) study of DNA-AgNCs structure in solution, as well as the production of circular oligonucleotide hairpins that support amodel with an interfacial binding motif for AgNCs.W ep ropose that AgNCs bridge two hairpin oligonucleotides,w here the self-assembly of the dimeric complex converts dark AgNCs into the highly fluorescent AgNC species.…”
Section: Introductionmentioning
confidence: 99%